Trajectory Control of Self‐Propelled Micromotors Using AC Electrokinetics. Issue 42 (27th August 2015) - Yoshizumi, Yoshitaka; Honegger, Thibault; Berton, Kevin; Suzuki, Hiroaki; Peyrade, David
Abstract : 3D control of the motion of self‐powered micromotors is demonstrated using AC electrokinetics by applying an AC electric field on indium tin oxide transparent electrodes.